Does Evolocumab use in Europe match 2019 ESC/EAS lipid guidelines? Results from the HEYMANS study. (25th November 2020) - Ray, K.K; Bruckert, E; Van Hout, B; Feudjo Tepie, M; Bridges, I; Sibartie, M
Abstract: Background: 2019 ESC/EAS dyslipidaemia guidelines recommend a 50% lowering in untreated LDL-C and use of PCSK9 inhibitors (PCSK9i) for patients at very-high cardiovascular (CV) risk when LDL-C target goals of <1.4 mmol/L or <1.0 mmol/L (for those with 2 CV events within two-years) are not met despite maximally tolerated statins and ezetimibe. Purpose: This observational study describes a cohort of patients initiating evolocumab across 10 EU countries. Methods: Patients are followed from evolocumab initiation (baseline). Demographic/clinical characteristics, lipid modifying therapy (LLT) and lipid values were collected from medical records (6 months prior to evolocumab initiation through 30 months post initiation). We report interim data from patients initiating evolocumab from August 2015 with follow-up through October 2019. Results: 1896 patients initiated on evolocumab as per local reimbursement criteria were included in this interim analysis (planned sample size: N=2, 000). Most (1663 [88%]) had 12 months follow-up, 665 (35%) had 18 months follow-up; mean follow-up, 16.3 months. Mean (SD) age was 60.0 (10.8) years; 85% of patients had a history of CV disease (CVD), 44% had a diagnosis of familial hypercholesterolemia (FH), 19% had type 2 diabetes, 66% were hypertensive, 7% had renal impairment and half (51%) were prior or current smokers. The majority (60%) reported statin intolerance and 42% were not receiving any LLT at evolocumab initiation. Fewer than half (805 [43%]) were receiving a statin (±ezetimibe) at evolocumab initiation; of these, most were on a high/moderate intensity (68%/22%). 12% of patients were receiving statin monotherapy. Median (Q1, Q3) baseline LDL-C was 3.98 (3.16, 5.06) mmol/L. Within 3 months of evolocumab initiation median LDL-C fell by 58% to 1.62 mmol/L. This reduction was maintained over time (Figure). Overall, 58% of patients achieved at least one LDL-C <1.4 mmol/L during follow-up. Among patients receiving background statins and/or ezetimibe at evolocumab initiation, 67% (667/990) achieved at least one LDL-C <1.4 mmol/L, compared with 43% (295/679) of patients not receiving background statins/ezetimibe. During follow-up, 39–46% patients received no background LLT, 40–44% received statin ±ezetimibe, 11–14% received statin monotherapy. Conclusion: In Europe, patients initiated on evolocumab had baseline LDL-C levels almost 3 times higher than the present threshold for PCSK9i use, reflecting local reimbursement criteria. Evolocumab resulted in a more than 50% reduction in LDL-C; however, only approximately half of all patients achieved an LDL-C <1.4 mmol/L. LDL-C goal attainment was higher among patients receiving evolocumab with background LLT, suggesting that achievement of EAS/ESC LDL-C goals requires multiple LLTs and a lower threshold for PCSK9i initiation. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Amgen